2009
DOI: 10.1002/ptr.2802
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic investigation of chromosomal aberrations in cells treated with plantamajoside from Plantago asiatica

Abstract: Plantago asiatica is a member of the Plantaginaceae family, and is widely distributed in East Asia. In our previous work, a single active compound, plantamajoside was isolated and confirmed to have glycation inhibitory activity, and did not possess toxicity during a 90 day repeated oral toxicity test in rats. In the present study, a chromosomal aberration test was performed to investigate the genotoxicity of plantamajoside. From the results of the cytotoxicity test, plantamajoside proved to be less toxic when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Antioxidant effects were also tested using DPPH (diphenylpicrylhydrazyl) radical scavenging activity (Miyase et al, 1991;Jimé nez and Riguera, 1994;Skari et al, 1999;Chen et al, 2010) and oxygen radical absorbance capacity (ORAC) (Amakura et al, 2012). Cytotoxic activity was measured using S9 Cell fraction (Koo et al, 2009), or cell line A549 (human lung carcinoma), HL-60 (human promyelocytic leukemia) and P388 (murine leukemia) . The activity against flatoxin B1-induced cytotoxicity in H4IIE cells (Lee et al, 2006a) was also determined.…”
Section: Bioactivities Of Plantamajosidementioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidant effects were also tested using DPPH (diphenylpicrylhydrazyl) radical scavenging activity (Miyase et al, 1991;Jimé nez and Riguera, 1994;Skari et al, 1999;Chen et al, 2010) and oxygen radical absorbance capacity (ORAC) (Amakura et al, 2012). Cytotoxic activity was measured using S9 Cell fraction (Koo et al, 2009), or cell line A549 (human lung carcinoma), HL-60 (human promyelocytic leukemia) and P388 (murine leukemia) . The activity against flatoxin B1-induced cytotoxicity in H4IIE cells (Lee et al, 2006a) was also determined.…”
Section: Bioactivities Of Plantamajosidementioning
confidence: 99%
“…Enzyme inhibitory activity was determined using cAMP phosphodiesterase from beef heart and 5-lipooxygenase from RBL-1 cells (Deyama et al, 2006;Nishibe, 1994Nishibe, , 2002Skari et al, 1999). Genotoxicity was determined using the chromosomal aberration test (Koo et al, 2009), induction of glutathione S-transferase (GST) (Lee et al, 2006a), inhibitory activity against edema was demonstrated using arachidonic acid-induced mouse ear oedema (Deyama et al, 2006;Nishibe, 1994Nishibe, , 2002 and cAMP phosphodiesterase was used to demonstrate enzyme activity (Ravn et al, 1990;Jimé nez and Riguera, 1994) and enzyme inhibitory effects were further investigated on 5-lipoxygenase (Ravn et al, 1990) and enzymatic lipid peroxidation (Skari et al, 1999). The pathogenesis of diabetes was measured by testing glycation inhibitory activity (Choi et al, 2008), and prevention of diabetic complications (Won et al, 2007).…”
Section: Bioactivities Of Plantamajosidementioning
confidence: 99%
See 1 more Smart Citation
“…The increasing use is more and more supported by the cumulating body of evidence of pharmacological, chemical studies and clinical trials. Chemical studies are inherent parts of evidence‐based phytotherapy—they are accomplished to prove effectiveness of the products, to help their characterization and standardization, and to aid toxicology studies . Therefore, development of methods capable of quantifying these compounds is a constant task for research.…”
Section: Introductionmentioning
confidence: 99%